2010
DOI: 10.1002/hlca.201000046
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis, Characterization, and Antibacterial Activities of Novel Isosteviol Derivatives with D‐Ring Modification

Abstract: Considerable interests have been attracted by isosteviol and its derivatives because of their large variety of bioactivities. In this project, a series of novel 15-and 16-substituted isosteviol derivatives were stereoselectively prepared by means of functional interconversions in ring D of the tetracyclic diterpene isosteviol. All compounds synthesized were characterized by analysis of NMR, IR, HR-MS data, and the configurations of 33 and 37 were confirmed by X-ray crystallographic analysis. The antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 29 publications
0
31
0
1
Order By: Relevance
“…On the other hand, treatment of 1 with NaIO 4 and KOH produces steviol (2; (5b,8a,9b,10a,13a)-13hydroxykaur-16-en-18-oic acid) [4], a kaurane-type diterpenoid which constitutes an aglycone moiety of 1. On the other hand, a number of derivatives of 2 and 19 have been prepared and evaluated for their bioactivities which included anti-inflammatory [7 -9], cytotoxic [10 -12], antibacterial [10] [13], glycosidase-inhibitory [14] [15], plantgrowth-regulation [16], antihyperglycemic [17], and glucocorticoid-agonist activities [18]. In addition, compounds 1, 2, and 19 have been suggested to be valuable chemopreventive agents against chemical carcinogenesis [5] [6].…”
Section: Introduction -Steviosidementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, treatment of 1 with NaIO 4 and KOH produces steviol (2; (5b,8a,9b,10a,13a)-13hydroxykaur-16-en-18-oic acid) [4], a kaurane-type diterpenoid which constitutes an aglycone moiety of 1. On the other hand, a number of derivatives of 2 and 19 have been prepared and evaluated for their bioactivities which included anti-inflammatory [7 -9], cytotoxic [10 -12], antibacterial [10] [13], glycosidase-inhibitory [14] [15], plantgrowth-regulation [16], antihyperglycemic [17], and glucocorticoid-agonist activities [18]. In addition, compounds 1, 2, and 19 have been suggested to be valuable chemopreventive agents against chemical carcinogenesis [5] [6].…”
Section: Introduction -Steviosidementioning
confidence: 99%
“…To clarify the efficacy of the 13-OH group on the cytotoxicity, we prepared ent-kaur-16-en-19-ol 19-O-cinnamate (18), the 13-deoxy analog of 5, from ent-kaur-16-en-19-oic acid (15), which has been isolated previously from the pollen of Helianthus annuus [21]. ii) Benzyl chloride (BnCl)/pyridine; 9% (13). 16) and then reduced with LiAlH 4 to yield 17.…”
Section: Introduction -Steviosidementioning
confidence: 99%
“…It has been shown that chemical transformations of the isosteviol core can be frequently performed in a stereoselective manner in the absence of any enantioselective catalysts or chiral auxiliaries [16,21]. The high stereoselectivity of those reactions can be attributed to the unique space structure of the rigid isosteviol skeleton with several chiral centers.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, series of pyrazoline [15], pyrazole [15] and isoxazolidine [16] derivatives (Figure 1) have been recently synthesized.…”
mentioning
confidence: 99%
“…(–)‐Isosteviol ( 2 ), being a metabolite of stevioside, also exhibits a wide range of biological activities, which might be the reason why the EU has reluctantly accepted stevioside as an alternative sweetener. Compound 2 can induce insulin regulation7 and exhibits cardioprotective8 as well as cytotoxic9 and antibacterial effects 10. During the past few years, (–)‐isosteviol has become a focus in organic chemistry for two major reasons.…”
Section: Introductionmentioning
confidence: 99%